1996
DOI: 10.1093/oxfordjournals.ndt.a027522
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin inhibits lipopolysaccharide-induced NF-kB activation in human mesangial cells

Abstract: These data suggest an additional mechanism by which HMG-CoA reductase inhibitors may reduce glomerular injury, namely, by inhibiting NF-kappaB activation and the subsequent proliferative and inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 0 publications
3
14
0
1
Order By: Relevance
“…It was also revealed that increased NF-κB activation in mesangial cells correlates with increased expression of a variety of inflammatory genes such as interleukins IL-1β IL-6 and IL-8, tumor necrosis factor α (TNF-α) monocyte chemoattractant protein-1 (MCP-1), interferon invasive protein-10 (IP-10), and inducible nitric oxide synthase [2,10,[19][20][21][22][23]. In addition to the proinflammatory actions of NF-κB, some data, similarly as our study, support a role for NF-κB in the control of mesangial cell proliferation [2,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 74%
“…It was also revealed that increased NF-κB activation in mesangial cells correlates with increased expression of a variety of inflammatory genes such as interleukins IL-1β IL-6 and IL-8, tumor necrosis factor α (TNF-α) monocyte chemoattractant protein-1 (MCP-1), interferon invasive protein-10 (IP-10), and inducible nitric oxide synthase [2,10,[19][20][21][22][23]. In addition to the proinflammatory actions of NF-κB, some data, similarly as our study, support a role for NF-κB in the control of mesangial cell proliferation [2,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 74%
“…There is now evidence to support the view that besides having a major lipid-lowering effect, statins also have an antiinflammatory effect, 39 probably acting through modulation of NF--B activity. 40,41 Thus, part of the reduced influence of the stromelysin genotype on disease progression in treated Mean (95% CI) IMT of carotid bifurcation according to combined genotype of stromelysin-1 5A/6A and IL-6 G/C polymorphisms; 5 and 6 refer to 5A and 6A alleles of stromelysin-1 polymorphism; C and G refer to IL-6 alleles. Adjusted for age, cardiorespiratory fitness, body mass index, smoking, LDL cholesterol, and systolic blood pressure and for sonographers.…”
Section: Discussionmentioning
confidence: 99%
“…24 Decreased NF-B activity in mesangial cells has been detected on treatment with lovastatin, 25 whereas simvastatin has been found to increase NF-B activation in endothelial cells. 26 Our investigations, being the first to use transient transfection techniques and to compare different statins at various concentrations, clearly support the notion that HMG-CoA reductase inhibitors curtail NF-B signaling.…”
Section: Dichtl Et Al Statins and Transcription Factorsmentioning
confidence: 99%